PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INKUIRI TERBIMBING BERBANTUAN TEKNIK MIND MAPPING UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KEMAMPUAN BERPIKIR KREATIF SISWA SMP - Erna Suhartini; Z. A. Imam Supardi; Rudiana Agustini (Universitas Negeri Surabaya, 2017)
The purpose of this research is producing physics learning material through guided inquiry model with Mind Mapping technique that valid, practical, and effective to improve comprehension of concept and creative thinking ability of student in junior high school. The development of learning material used the Kemp model and was try outed in class VII of SMP Al Azhar Syifa Budi Samarinda, second semester in academic year 2013/2014 with One-Group Pretest-Posttest Design. The data collection used observation method, test, and quetionnaires. The data analysis techniques used quantitative descriptive analysis. The results of this research are: 1) Learning material developed has a valid category; 2) The practicality of learning material in terms of a good category in feasibility of lesson plans and the students activities in accordance with steps of guided inquiry model with Mind Mapping technique; and 3) The learning material effectiveness in terms of: (a) Improving students comprehension of concept seen from the N-gain score with high category; (b) Improving creative thinking ability of student by getting the N-gain score with high category; and (c) The students responds toward material and implementation of learning are very positive. Its conclusion that the learning material through guided inquiry model with Mind Mapping technique are decent to improve comprehension of concept and creative thinking ability of student in junior high school. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran fisika model inkuiri terbimbing berbantuan teknik mind mapping yang valid, praktis dan efektif (layak) untuk meningkatkan penguasaan konsep dan kemampuan berpikir kreatif siswa SMP. Pengembangan perangkat pembelajaran menggunakan model Kemp dan diujicobakan di kelas VII SMP Al Azhar Syifa Budi Samarinda semester genap tahun ajaran 2013/2014 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif. Temuan hasil penelitian, yaitu: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Kepraktisan perangkat pembelajaran ditinjau dari keterlaksanaan RPP berkategori baik dan aktivitas siswa sesuai dengan tahap-tahap pada model inkuiri terbimbing berbantuan teknik mind mapping; dan 3) Keefektifan perangkat pembelajaran ditinjau dari: (a) Peningkatan penguasaan konsep siswa yang terlihat dari N-gain dengan kategori tinggi; (b) Peningkatan kemampuan berpikir kreatif siswa yang terlihat dari N-gain dengan kategori tinggi; dan (c) Respon siswa terhadap perangkat dan pelaksanaan pembelajaran sangat positif. Simpulan dari penelitian ini adalah perangkat pembelajaran model inkuiri terbimbing berbantuan teknik mind mapping yang dikembangkan layak untuk meningkatkan penguasaan konsep dan kemampuan berpikir kreatif siswa SMP.